A System of General Purpose Computer Programs for Information Retrieval in the Behavioral Sciences. - Vinsonhaler, John F. (American Behavioral Scientist)
Focuses on the need for Basic Indexing and Retrieval System (BIRS) to be adapted to university computing installations. Reason for the rapid development of statistical data processing; Summary of the component programs of the BIRS; Examples of how the system is used.